El misterio de seducir a través de los sentidos lencería (2017)
Since ancient times sexuality has always existed and was an issue which represented many taboos, today many of these taboos before sex continue; However, in the last years the new generations have made a change with respect to sex, it is spoken more naturally as an action of the human being. In the last 8 years the sex shop has arrived with great force, which offers erotic lingerie, complementary articles such as stockings, whips, stimulating and body oils etc, and at the same time offers sex toys. This project seeks to merge textile technology, lingerie, aromatherapy and a bit of color psychology, resulting in an intimate and luxurious lingerie product with a functional textile, which has micro capsules with aromas which help Achieve sexual stimulation in the couple, increasing sexual desire and finally taking into account different colors that have an effect on the brain of people and this causes certain reactions and at the same time each color has a perception at the time of seeing it. Bringing together all this creates the brand "Mystère" which is a brand that will handle 3 different lines and a functional line, which cover different designs of lingerie, differentiating us from the rest of the market with our product with micro capsules to help stimulate the Sexual desire in couple